The Relationship Between Perceived Transformational Leadership Style and Organizational Commitment in Kindergarten Teachers - Triyana Triyana; Erni Munastiwi; Siti Marpuah (PROGRAM STUDI MAGISTER PENDIDIKAN ISLAM ANAK USIA DINI (PIAUD) FAKULTAS ILMU TARBIYAH DAN KEGURUAN UIN SUNAN KALIJAGA YOGYAKARTA, 2023)
This study aims to determine the positive relationship between perceptions of the principal's transformational leadership style and organizational commitment in teachers/educators. Organizational commitment should be owned by every teacher/educator to achieve the goals of the educational institution listed in the vision and mission of the educational institution. However, commitment to the organization could be more concern for educational institutions. This study is to fill the literature gap and provide direction to stakeholders as a consideration for making references regarding transformational leadership style and teacher organizational commitment. The data collection method in this study used a scale with the Likert Model scale scoring technique. The hypothesis in the study is that there is a relationship between the perception of the principal's transformational leadership style and the teachers' organizational commitment. The population and sample in the study were all educators in kindergartens in Cilacap District, totaling 30 teachers/educators. Data collection methods using the Transformational Leadership Style scale and Organizational Commitment scale. The results of the Pearson Product Moment correlation analysis of the two variables amounted to (rxy) 0.402 (p < 0.014). The results showed a positive and very significant relationship between the perception of transformational leadership style and organizational commitment in teachers in kindergarten. The coefficient of determination of the correlation coefficient is R2 = 0.162. The conclusion from the data presented shows that leadership style provides an effective contribution to organizational commitment in teachers by 16.2%. The usefulness of this research is the need and importance of leadership style to determine the organizational commitment attached to teachers.